The Inheritance of Educational Inequality among Young People in Developing Countries - Francesco Pastore; Federica Roccisano (Institute for the Study of Labor (IZA), 2015)
This letter provides new evidence on the extent of the inheritance of educational inequality in the eight developing countries (Azerbaijan, China, Egypt, Iran, Kosovo, Mongolia, Nepal, Syria) where the ILO carried out the first wave of School-to-Work Transition survey. We observe different patterns of correlation between the level of intergenerational mobility, the educational upgrade and the role of parents' in sons' and daughters' education.
Keywords: D63; H52; I24; P46; P52; 330; intergenerational mobility; educational persistence; developing economies